Strengthening the knowledge of PAUD teachers about character education through living values education in Bengkalis Regency - Zein, Mas'ud; Iskandar, Edi; Azizah Azzahrah Rahmadan; Cindy Putri Andini; Thahir, Musa (Universitas Lancang Kuning, 2023)
This service aims to analyze the effect of Character Education training on increasing the competence of Early Childhood Education (PAUD) teachers in implementing character and morality values ​​in PAUD learning. The study was conducted involving 20 PAUD teachers in Bengkalis Regency. The evaluation results show that the training was successful in increasing PAUD teachers' knowledge, skills and understanding of Character Education and Living Values ​​Education. However, there is still potential to further strengthen the integration of the concept in daily practice. The evaluation results also indicate that the training program has a positive impact on the quality of teacher teaching and can create changes in the character and behavior of PAUD children. This research provides important insight into the importance of Character Education training in the context of PAUD education.